Targeted treatment in a case series of AR+, HRAS/PIK3CA co-mutated salivary duct carcinoma - Rieke, Damian T.; Schröder, Sebastian; Schafhausen, Philippe; Blanc, Eric; Zuljan, Erika; von der Emde, Benjamin; Beule, Dieter; Keller, Ulrich; Keilholz, Ulrich; Klinghammer, Konrad (Frontiers in Oncology, 2023)
Background and purpose A subgroup of salivary duct carcinoma (SDC) harbor overexpression of the androgen receptor (AR), and co-occurring mutations in the HRAS- and PIK3CA-genes. The impact of genomic complexity on targeted treatment strategies in advanced cancer is unknown. Materials and methods We analyzed molecular and clinical data from an institutional molecular tumor board (MTB) to identify AR+, HRAS/PIK3CA co-mutated SDC. Follow-up was performed within the MTB registrational study or retrospective chart review after approval by the local ethics committee. Response was assessed by the investigator. A systematic literature search was performed in MEDLINE to identify additional clinically annotated cases. Results 4 patients with AR+ HRAS/PIK3CA co-mutated SDC and clinical follow-up data were identified from the MTB. An additional 9 patients with clinical follow-up were identified from the literature. In addition to AR overexpression and HRAS and PIK3CA-alterations, PD-L1 expression and Tumor Mutational Burden > 10 Mutations per Megabase were identified as additional potentially targetable alterations. Among evaluable patients, androgen deprivation therapy (ADT) was initiated in 7 patients (1 Partial Response (PR), 2 Stable Disease (SD), 3 Progressive Disease (PD), 2 not evaluable), tipifarnib was initiated in 6 patients (1 PR, 4 SD, 1 PD). One patient each was treated with immune checkpoint inhibition (Mixed Response) and combination therapies of tipifarnib and ADT (SD) and alpelisib and ADT (PR). Conclusion Available data further support comprehensive molecular profiling of SDC. Combination therapies, PI3K-inhibitors and immune therapy warrant further investigation, ideally in clinical trials. Future research should consider this rare subgroup of SDC.